Dynamics of retronasal aroma perception during consumption: Cross-linking on-line breath analysis with medico-analytical tools to elucidate a complex process - Büttner, Andrea; Otto, Sabine; Beer, Ambros; Mestres, Montse; Schieberle, Peter; Hummel, Thomas (Food Chemistry, 2008)
An analytical concept is developed for the on-line investigation of the temporal and spatial dynamics in ortho- and retronasal odor perception. It aims at the elucidation of the relationship between the molecular level and perception during and after administration of a chemical stimulus. One basic principle is to apply precisely defined odorous stimuli, and to measure their temporal characteristics using an on-line analytical technique, proton-transfer reaction mass spectrometry (PTR-MS). In parallel, the subjects’ response to the stimulus can be investigated with electrophysiological and psychophysical techniques. This approach can be modified to elucidate the processes involved in the perception of food and drinks. Panellists may take an active role as they modulate chemosensations with certain patterns of mastication/swallowing. Using videofluoroscopy or real-time magnetic resonance imaging these mechanical oropharyngeal processes may be visualized.<br